2011
DOI: 10.4049/jimmunol.1100198
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD180 (RP105) Activates B Cells To Rapidly Produce Polyclonal Ig via a T Cell and MyD88-Independent Pathway

Abstract: CD180 is homologous to TLR4 and regulates TLR4 signaling, yet its function is unclear. We report that injection of anti-CD180 mAb into mice induced rapid Ig production of all classes and subclasses except IgA and IgG2b, with up to 50-fold increases of serum IgG1 and IgG3. IgG production after anti-CD180 injection was not due to reactivation of memory B cells and was retained in T cell-deficient (TCR KO), CD40 KO, IL-4 KO and MyD88 KO mice. Anti-CD180 rapidly increased both transitional and mature B cells, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 33 publications
(42 reference statements)
3
59
1
Order By: Relevance
“…Anti-RP105 has not been tested in humans; however, it was recently shown in a mouse model that i.v. anti-RP105 Abs induced Ig production of several subclasses and was well tolerated by the mice (20). mAbs are now being used routinely in the treatment of diseases such as cancer and rheumatoid arthritis, and there is no obvious reason why humanized anti-RP105 Abs should not be tested for treatment of CVID.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-RP105 has not been tested in humans; however, it was recently shown in a mouse model that i.v. anti-RP105 Abs induced Ig production of several subclasses and was well tolerated by the mice (20). mAbs are now being used routinely in the treatment of diseases such as cancer and rheumatoid arthritis, and there is no obvious reason why humanized anti-RP105 Abs should not be tested for treatment of CVID.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies reported defective TLR9 signaling in CVID-derived B cells (15)(16)(17); recently, defective signaling from TLR9 in combination with RP105 (CD180) was reported in three CVID patients (18). The natural ligand for RP105 has not been identified, but anti-RP105 Abs are potent activators of RP105 both in vitro (19) and in vivo (20).…”
Section: Ommon Variable Immunodeficiency (Cvid) Is the Most Commonlmentioning
confidence: 99%
“…In a recent paper (Chaplin et al 2011), differentiation from transitional to mature B cells was induced by stimulation with CD180 (RP105), a toll-like receptor (TLR)-4 homologue expressed by monocytes, macrophages, dendritic cells, and B lymphocytes which regulates TLR-4 signaling and induces B cell proliferation.…”
Section: Cd24mentioning
confidence: 99%
“…CD180/RP105 is a membrane-associated orphan receptor that drives normal human and mouse B-cell activation and proliferation (11)(12)(13)(14). Anti-CD180 monoclonal antibody (mAb) induces upregulation of MHC class II, CD40 and CD80/CD86 on human and mouse B cells (4,11,15) and differentiation and rapid secretion of immunoglobulin G (IgG) in vivo (16). We have shown previously that approximately 60% of CLL samples express CD180.…”
Section: Introductionmentioning
confidence: 99%